The Concept of Improvement of Communication Trends in the Development of Tourism in Conditions of Digital Transformation of Society (Laisvalaikio tyrimai, 2018)
Relevance of the study of the concept of improving communication trends in the development of tourism in the context of the digital transformation of society is in the fact that the problem of trends is a completely new and a unique one, which is gaining increasing importance in the conditions of the fourth industrial revolution. In modern conditions, methods, methodology and mechanisms of communication trends in tourism development, information technologies in tourist companies and organizations, application of digital transformation of business tourism and transformation of business models of tourism (green, rural, timed to events, etc.) are improved. The problem of research is the allocation of new communication trends in the development of tourism, and the use of information technology and digital tourism economy as a new driver of the information society, technological development in Ukraine and the use of special software, innovative and financial tools, and the Internet promotion of tourist products to foreign markets. Objectives and tasks of research: formation of the concept of improvement of communication trends in the development of tourism business, aimed at further integration of Ukraine into the international division of labour. It is tourism that influences the development of all relations in the conditions of globalization and information society and becomes the most demanded product in the market of services. The purpose is to form the concept of improving communication trends in the development of tourism in the conditions of digital transformation of society. Methods and methodology of research. The article uses socio-psychological methodology of studying the model of tourism and communication technologies, which deepen the essence and content of tourism as a complex sociocultural phenomenon. In other words, the model and the process of its construction of the business model of tourism and tourism activity are the cognitive basis of the constructivist methodology as a cultural process, the basis of which is the study of “genuinely human existence”, necessary for the self-realization of the individual. The result of the study. Tourism is called to be the arena of spiritual self-improvement of people, their spiritual development. In tourism, man finds the embodiment of the highest non-essential values created by civilization, the factor of integration of society, the system of means by which the tourist activity of people is regulated. Tourism is the formation and satisfaction of demand in the so-called “space of free time” or leisure space. Tourism today acts as a sociocultural, effective management technology, which formulates the basic principles and approaches to building a modern tourism business as a socio-cultural process. Conclusions. The main task in modern conditions is the cultivation of the tourism industry 4.0 in Ukraine, the Internet promotion of the original national tourist product to foreign markets and the use of the digital economy, including management, technology, and security.Keywords: tourism, tourism activity, digital economy, tourist brand, information technologies, digital transformation.